Meditations on the divine liturgy: boundaries of the theatricality in the creative work of Nikolay Gogol - Vidugirytė, Inga (Literatūra, 2015)
The purpose of the present article is to demonstrate the theatricality of Gogol’s Meditations on the Divine Liturgy. Theatricality is “the language of theatre as art”, as Jurij Lotman has stated. Phillis Hartnoll points out three aspects, viz. an actor, a dialogue, and a spectator, that separate theatre from its origins – the ritual. The birth of the spectator seems to Lotman and to Boris Uspenskij to be the decisive factor to establish a situation of the performance. The visuality of the performance is the main feature of theatre as art. There are three presumptions Gogol has about liturgy: (1) liturgy is a dramatic form of the evangelical plot, (2) the forms of worship in liturgy are so perfect that watching them is enough to understand the meaning of the ritual, (3) in liturgy, it is possible to achieve the unity of souls and feelings of all participants of the ritual. Gogol presents liturgy as performance. The narrative is based on separate scenes with clearly marked beginnings and ends. Gogol even renders intonations of dialogues between a priest and a deacon. The motif of performing distinguishes Gogol’s work from his predecessors. The only point of view in the text is from the outside. The narrator is one of the spectators of liturgical performance. On the other hand, the narrator is also a participator of the worship. Gogol shows the effect the performance makes on people and also renders their praying. Taking the sacrament is described as catharsis and in the same terms as Aristotle has done, viz. the horror and the purging. So even at this moment the theatrical nature of liturgy is retained. In the context of the Gogol’s discourse of theatre, liturgy seems to be the ideal performance. One can presuppose that the writer’s wish to explain the role of the theatre has ended with describing the most spectacular performance of the orthodox ritual. In doing this the writer was most likely influenced by the Ukrainian baroque tradition which shaped Gogol’s artistic imagination. The theatricality of the baroque aesthetics found its place in the visual nature of Gogol’s texts. In his search for new creative forms Gogol was not alone. In 1842–1843 Adam Mickiewicz pointed to the Greek tragedy and to the mysteries of the Middle Ages as possible examples to follow in the future Slavonic theatre. By demonstrating the theatrical possibilities of the Christian ritual Gogol was close to these ideas.